AUDITING AND STATISTICS– INTERDISCIPLINARY TEACHING CONCEPT - Hindls, Richard; Hronová, Stanislava (European Scientific Journal, ESJ, 2015)
This paper explores educational aspects of teaching statistics to auditors and controllers. It specifically focuses on employing certain methods of statistical inference in auditing, predominantly from the viewpoint of illuminating the relevant fields of statistics to university students of auditing. Key sections of this paper deal with teaching confidence intervals and Benford’s Law to auditors.